Peran Guru Sejarah dalam Mengatasi Krisis Moral Siswa Melalui Pembelajaran Sejarah dengan Pendidikan Karakter di Madrasah Aliyah Tahfizhil Quran - Selviana, Anita; Nababan, Surya Aymanda; Sumantri, Pulung; Nugraha, Muhammad Adika; Azis, Abdul; Darma, Aditya (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
The moral crisis faced by students today is a serious issue in the field of education. One strategy that can be used to address this problem is by integrating history education with character education in Madrasahs. This research aims to evaluate the role of history teachers in addressing students' ethical crisis through history education with character education in Madrasah Aliyah Tahfizhil Quran. The research method used is qualitative research with a case study approach. Data is collected through classroom observations, interviews with history teachers, and analysis of documents related to the history education and character education programs in Madrasah Aliyah Tahfizhil Quran. The data is then analyzed descriptively and interpretatively to obtain a comprehensive understanding of the role of history teachers in addressing students' ethical crisis. The research findings show that history teachers play an important role in addressing students' ethical crisis through history education with character education. History teachers not only convey historical facts but also build ethical awareness and promote positive values in students. They use interactive and contextual teaching methods and utilize historical sources that are relevant to the desired character values. In addition, Madrasah Aliyah Tahfizhil Quran has implemented an integrated character education program with history education. This program includes values such as honesty, cooperation, tolerance, and mutual respect. History teachers act as facilitators in guiding students to understand and internalize these character values through history education. Therefore, it can be concluded that the role of history teachers in addressing students' ethical crisis is crucial. Teachers are the main pillar of education in the world.